Pengembangan Metode Prediksi Produksi Air DAS untuk Sungai-sungai Utama di Aceh - Husnan Husnan; Hidayat Pawitan; Gatot Irianto; Kukuh Murti Laksono; Hairul Basri (Fakultas Pertanian, Universitas Syiah Kuala, 2008)
Developing Prediction Method of Watershed for Main Rivers in AcehABSTRACT. The conversion of rural land to urban land usually increases erosion, discharge and volume of storm runoff in watershed. It also causes other problem that effect soil and water. An urban or urbanizing watershed is one in which impervious surface cover or will soon cover a considerable area. Impervious surface includes roads, side walk, parking lots and building. Natural flow paths in the watershed may be replaced or supplemented by paved gutters, storm sewers or other elements of artificial drainage. Hydrologic studies to determine runoff and peak discharge should ideally be base on long-term stationary stream flow records for the area, such records are seldom available for small drainage areas. Even were they are available, accurate statistical analysis of them is usually impossible because of the conversion of land to urban uses during period of record. It therefore is necessary to estimate peak discharge with hydrologic models based on measurable watershed characteristics. Only through understanding of these characteristic and experience in using these models can be make sound judgments on how to alter model parameter to reflect changing watershed conditions.